Addressing Mental Health Challenges Among Overseas Chinese Students: Fostering Belonging and Community Support - Zhihui Yang (Art and Society, 2024)
This article discusses the mental health problems of overseas Chinese students, and by citing a number of studies and cases, it reveals the serious challenges faced by this group. The article first identifies a series of factors that contribute to the mental health problems of overseas Chinese students, such as the New Crown Epidemic, racial discrimination, and economic pressures, and discusses their difficulties in seeking psychological help. The article then focuses on the importance of building an active community to foster a sense of belonging, and proposes a series of interventions, including the creation of community exchange platforms, the provision of counselling services, and the encouragement of participation in activities. Finally, the article calls for increased attention and research on the mental health issues of overseas Chinese students and suggests directions for future guidance.